Suitability assessment and Greenway planning in Cegléd micro-region, Hungary - Sándor Jombach; Ágnes Sallay (Fábos Conference on Landscape and Greenway Planning, 2025)
Greenways help to draw the attention to particularly valuable sites or to sites with less priorities and advantages too. Greenways are valuable for wildlife as involving corridors and core areas provide a complex habitat for nature and are precious for human recreation as well. The term greenway can be considered as a tool in planners hand (Ahern 1995) to propose a safe, healthy, environmental friendly neighborhood. In Hungary the greenway movement has the aspect to link leisure activities with healthy lifestyle and food, agricultural products, handicrafts and other products. Greenways offer a cooperation among partners in the countryside from vineyards to tourist accommodations. Many greenways in Hungary are along creekside landscapes. The case was similar in Cegléd micro-region where our clients plan and partly run an organic farm of 12 hectares that has important role in education and social employment too. Even then the site has significant ecological values, with a stream and officially designated ecological corridor. During our field work combined with mapping and analysis we aimed to assess the suitability of the routes near the organic farm for greenway development purpose. The road network between the town Cegléd and the village Ceglédbercel was explored, assessed and mapped through partly by students, in order to investigate the possibility of connecting the two settlements with a non-motorized route. The goal is to provide leisure activity for the visitors of the neighboring thermal spa. First within 32 km2 we selected all the possible routes. Based on a review of the road network, we have preliminarily mapped most of the routes by walk, and have identified those routes suitable for greenway development (58 km). The routes were assessed according to several test criteria, including the road surface and the surrounding area. The main assessment criteria were the type and quality of pavement (+ kerbing, drainage), street lighting, traffic safety, vegetation (both sides), landscape character and the ability to provide rest areas. During the field survey, we focused on ensuring that the future greenway would pass through a variety landscape character types. Our recommendations for each road section include improving the quality of the road, improving the roadside vegetation (thereby increasing shade) and improving stops and resting places. The proposed route includes road sections that can be converted into greenways with minimal development. In the medium term, it is recommended that the creekside route, should be developed as a very attractive feature of the area. With these principles in mind, we can conclude that the development of the Organic farm can benefit more from the town’s residents by designating a greenway.
Keywords: greenway; suitability; capability; assessment